(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2020)
This review is dedicated to «Genesis» 47 (2018). «Genesis» is a six-monthly magazine in French, promoted by the Institut des textes et manuscrits modernes (ITEM) in Paris, the center of studies and reflections on genetic criticism. This number, entitled " Entrer en listes " and edited by Rudolf Mahrer, Gaspard Turin and Monica Zanardo, is available online at the following address: https://journals.openedition.org/genesis/1722